Examples of Different Reactions of Benzylsulfanyl‐Substituted Alkynes with Selected Complexes of TiII and CoI. Issue 24 (17th June 2013) - Altenburger, Kai; Semmler, Julia; Arndt, Perdita; Spannenberg, Anke; Meel, Matthias J.; Villinger, Alexander; Seidel, Wolfram W.; Rosenthal, Uwe
Abstract: Reactions of the group 4 metallocene alkyne complexes [Cp2 M(L)(btmsa)] (Cp = η 5 ‐cyclopentadienyl = η 5 ‐C5 H5, btmsa = η 2 ‐Me3 SiC2 SiMe3 ;1 : M = Ti, L = none;2 : M = Zr, L = pyridine) and of the [(triphos)Co I ] moiety [triphos = 1, 1, 1‐tris(diphenylphosphanylmethyl)ethane] with the benzylsulfanyl‐substituted acetylenes PhCH2 S–C2 –SCH2 Ph (3 ) and PhCH2 S–C2 –SFmoc (4 ) (Fmoc = fluorenylmethoxycarbonyl) have been investigated. Complex1 reacted with3 to give a mixture of a violet solid and [Cp2 Ti(SCH2 Ph)2 ] (5 ). Subsequently, the violet solid transformed in toluene at 70 °C into the dinuclear complex [(Cp2 Ti)2 (μ‐κ 2 ‐κ 2 ‐BnSC4 SBn)] (6 ) displaying two [Cp2 Ti] moieties bridged by a 1, 4‐bis(benzylsulfanyl)‐1, 3‐butadiyne in the trans configuration. Complex6 was further degraded in toluene at 100 °C to the tetranuclear cluster [CpTiS]4 (7 ). Similar reactivity was deduced indirectly for the reaction partners1 /4 and2 /3 . For Co I, the side‐on alkyne complexes [(triphos)Co(3 )](PF6 ) (9 ‐PF6 ) and [(triphos)Co(4 )](PF6 ) (10 ‐PF6 ) were obtained. Reductive removal of the benzyl groups in9 ‐PF6 and subsequent coordination of the [Cp(PPh3 )Ru II ] + moiety led to the dinuclear complex [(triphos)Co(μ‐η 2 ‐κ 2 ‐C2 S2 )RuCp(PPh3 )] (13 ) displaying acetylene dithiolate (acdt 2– ) in a side‐on carbon–sulfur chelate coordination mode. In contrast, the reaction of10 ‐PF6 with piperidine under very mild conditions resulted in the thio‐alkyne complex [(triphos)Co(PhCH2 SC2 S)] (11 ) bearing a terminal sulfur substituent at the coordinated alkyne. However, a subsequent rearrangement reaction led to the Co III dithiolene complex [(triphos)CoS2 C2 (NC5 H10 )(CH2 Ph)](PF6 ) (14 ‐PF6 ). The intricate rearrangement very likely involves a dinuclear Co species with a η 2 ‐κ 2 coordination of the C2 S2 moiety. Abstract : Sulfur‐substituted alkynes show contrasting behaviour in their reactions with Ti II and Co I . Whereas the Ti II centre in the titanocene η 2 ‐alkyne complex effects a cleavage of the alkyne Csp –S bond concomitant with C–C coupling, Co I in the [Co(triphos)] η 2 ‐alkyne complex leads to loss of the benzyl groups to give either a heterobimetallic Co/Ru acetylene dithiolate complex or a dithiolene complex.